2017
DOI: 10.1111/nph.14406
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐level anatomical characteristics explain high mesophyll conductance and photosynthetic capacity in sclerophyllous Mediterranean oaks

Abstract: Leaf mass per area (LMA) has been suggested to negatively affect the mesophyll conductance to CO (g ), which is the most limiting factor for area-based photosynthesis (A ) in many Mediterranean sclerophyll species. However, despite their high LMA, these species have similar A to plants from other biomes. Variations in other leaf anatomical traits, such as mesophyll and chloroplast surface area exposed to intercellular air space (S /S and S /S), may offset the restrictions imposed by high LMA in g and A in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 74 publications
8
75
1
1
Order By: Relevance
“…Similar results for SLA-thickness-A area -RGR relationships were found in our previous (greenhouse) study under both well-watered and dry treatments (Ramírez-Valiente and Cavender-Bares, 2017). Since leaf lamina thickness and mesophyll thickness are highly associated in oaks (e.g., Peguero-Pina et al, 2017), our results would support Niinemets (2015) hypothesis. “Multiple-trait” mixed models showed a significant effect of SLA on RGR even after taking A area into account.…”
Section: Discussionsupporting
confidence: 71%
“…Similar results for SLA-thickness-A area -RGR relationships were found in our previous (greenhouse) study under both well-watered and dry treatments (Ramírez-Valiente and Cavender-Bares, 2017). Since leaf lamina thickness and mesophyll thickness are highly associated in oaks (e.g., Peguero-Pina et al, 2017), our results would support Niinemets (2015) hypothesis. “Multiple-trait” mixed models showed a significant effect of SLA on RGR even after taking A area into account.…”
Section: Discussionsupporting
confidence: 71%
“…These structures represent an example of evolutionary convergence. They reduce water loss (Peguero-Pina et al, 2017) and they may be highly reflective, limiting the penetration of light to the photosynthetic apparatus and reaching the mesophyll (Agrawal et al, 2009; Camarero et al, 2012). Thereby they reduce the need of photoprotective pigments and antioxidants, supporting the photoprotective role of leaf pubescence in Mediterranean species (Morales et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Despite structural filtering of light and efficient protection against water lost of most sclerophyllous leaves, it has been proposed the existence of a trade-off between photosynthesis and LMA in relation with Leaf Economics Spectrum (Wright et al, 2004). It seems that mesophyll conductance (g s ) may be the most limiting factor for carbon assimilation, showing those leaves with highest LMA values, a reduction in CO 2 diffusion to the carboxylation sites (Flexas et al, 2014; Onoda et al, 2017; Peguero-Pina et al, 2017). This implies that plants with high LMA will generally show lower photosynthetic capacity and thus, may require higher levels of photoprotective metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Evans et al () concluded that g ias is so large that it is not a major determinant of g m in leaves. Instead, T cw and S c /S, which affect g liq , were thought to be the most important factors in the determination of the g m (Evans et al , Miyazawa et al , Terashima et al , Tosens et al , Tomás et al , Onoda et al , Peguero‐Pina et al ). Studies have shown that the rate of CO 2 diffusion is determined by the relative length and the tortuosity and porosity of the medium (Flexas et al , Peguero‐Pina et al , Tosens et al , Nadal and Flexas ).…”
Section: Resultsmentioning
confidence: 99%